Implementation of Abandoned Land Control In Badung Regency, Bali - Ni Nyoman Wulan Ratna Komala Sari; I Made Suwitra; Ni Made Jaya Senastri (PT Keberlanjutan Strategis Indonesia, 2026)
This study examines the implementation of abandoned land control and the legal protection for land rights holders in Badung Regency, Bali. The high incidence of abandoned land in the region, driven by rapid tourism and investment development, has posed challenges to land utilization and social justice. Although Government Regulation No. 48/2025 mandates land utilization within two years of rights issuance, many landholders fail to comply, resulting in lands being categorized as abandoned. Using empirical legal research with statutory, case, conceptual, and sociological approaches, the study applied qualitative data analysis. Findings indicate that despite the enactment of PP No. 48/2025, only a fraction of abandoned lands is processed effectively, primarily due to budget limitations and inter-agency coordination gaps. Legal protections, including prior notifications, exist but are insufficiently applied, raising concerns over justice and certainty for landholders. Recommendations include enhanced regulatory synchronization, stricter monitoring, and improved coordination among agencies.